IMPLEMENTASI MANAJEMEN PENINGKATAN MUTU BERBASIS SEKOLAH DI SEKOLAH DASAR KOTA TOMOHON - Lolowang, Roosye Marie (Educatio Christi, 2020)
This Research aims to lay open the Management Implementation of Improvementin Quality Based School (MPMBS) in Regional Elementary School Branch on Dutyin Tomohon City. This Research have type the character of descriptive of evaluationhaving the character of exploration. This Research Responder is all headmaster,each 2 people learn and school committee from each every school of taken asresearch object. Pursuant to result of inferential solution and research thatimplementation MPMBS at 9 school blaze the way in region Branch On Duty inTomohon City enough succeed the core important in transparency, independence,cooperation, accountability and continue program, where Elementary School ofPrivate Sector be at the category very success with the value 94,4%. While ifevaluated from background (context), input, process and also output, is henceconcluded by that ninth of the school own the potency which enough support theimplementation MPMBS.